2013
DOI: 10.3791/50077
|View full text |Cite
|
Sign up to set email alerts
|

Breathing-controlled Electrical Stimulation (BreEStim) for Management of Neuropathic Pain and Spasticity

Abstract: Electrical stimulation (EStim) refers to the application of electrical current to muscles or nerves in order to achieve functional and therapeutic goals. It has been extensively used in various clinical settings. Based upon recent discoveries related to the systemic effects of voluntary breathing and intrinsic physiological interactions among systems during voluntary breathing, a new EStim protocol, Breathing-controlled Electrical Stimulation (BreEStim), has been developed to augment the effects of electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 52 publications
(76 reference statements)
2
13
1
Order By: Relevance
“…We observed that BreEStim resulted in a general desensitization effect (measured by elevated electrical pain thresholds in both treated and nontreated hands), while there was no such effect, or even a general sensitization effect after EStim or voluntary breathing only 1719. The findings support preliminary clinical observations15,16 that BreEStim-induced analgesia is likely related to modification of the affective component, ie, central effect. This effect has been attributed to internal pain-coping mechanisms activated by EStim during the specific window of voluntary breathing 16…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…We observed that BreEStim resulted in a general desensitization effect (measured by elevated electrical pain thresholds in both treated and nontreated hands), while there was no such effect, or even a general sensitization effect after EStim or voluntary breathing only 1719. The findings support preliminary clinical observations15,16 that BreEStim-induced analgesia is likely related to modification of the affective component, ie, central effect. This effect has been attributed to internal pain-coping mechanisms activated by EStim during the specific window of voluntary breathing 16…”
Section: Introductionsupporting
confidence: 85%
“…The delivery is triggered by fast and deep voluntary inhalation. In recent case reports,15,16 we have shown that BreEStim is effective in reducing chronic neuropathic pain in people with paraplegia and above-the-knee amputation. In these cases, BreEStim was applied only to the median nerve in the arm.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations